Edukasi Deteksi Dini Kanker Payudara dan Sosialisasi Herbal Medicine Sebagai Pencegahan Kanker Payudara pada Siswi SMA Datuk Batu Hampar Pekanbaru - Delidios Arimbi; Dina Ramsky; Ami Amelia; Ade Febriani (STIKes Ibnu Sina Ajibarang, 2025)
Breast cancer is a malignant tumor that is formed from breast cells that grow and develop uncontrollably so that they can spread between tissues or organs near the breast or to other parts of the body. Female gender is the strongest breast cancer risk factor, certain factors increase the risk of breast cancer including increasing age, obesity, harmful alcohol use, family history of breast cancer, history of radiation exposure, reproductive history (such as age at the start of menstrual periods and gestational age first), tobacco use and postmenopausal hormone therapy. This service aims to reduce the death rate due to breast cancer by providing public health education to increase awareness among women regarding the signs and symptoms of breast cancer as well as increasing knowledge about herbal medicine (medicinal plants with high anti-oxidant content) as an effort to prevent breast cancer. The method used in this service is the socialization method, lectures, practice using media in the form of leaflets. The education material includes understanding breast cancer, signs and symptoms, risk factors for breast cancer, the importance of BSE and its steps as well as herbal medicine (medicinal plants with high anti-oxidant content) which can help prevent breast cancer.